Design, analysis, and fabrication of monoshock compressor / Othman Al Affan Abd Rashid - Abd Rashid, Othman Al Affan (2023)
In 1972, Yamaha introduce the Mono-shock single shock absorber rear suspension system on their motorcycles competing in the Motocross World Championships (1). The objective of this project is to make a user-friendly device for assemble and dissemble spring from monoshock system. Next, monoshock is very important in any vehicle to get the best comfort and safety on the road. This research is about creating device to compress monoshock spring. This system is support with big spring. To dissemble it, user should remove the spring. So, this device will help user to use less human energy and improve safety precaution while remove the spring and avoid any injuries. In this research, all the fabricated steps already been applied to make the real prototype. After completing the project of monoshock compressor, it finally can function as it should be which can compress the monoshock spring safely and the objective been achieved